Reconciling food law to competitiveness report on the regulatory environment of the European food and dairy sector - Meulen, B. M. J. van der (European Institute for Food Law series, 2009)
"The food sector is the third most regulated industry in the EU. It is the most important production sector, but its competitiveness and innovativeness are under pressure. This book reports on a legal research into the question if there is a connection between the sector's declining innovativeness and competitiveness on the one hand and the increasing regulatory burden on the other hand. The aim is to indicate opportunities to remove avoidable obstacles for the food industry in general and small and medium enterprises in particular. The book brings to light several shortcomings in the regulatory framework and makes concrete recommendations for simplifying and improving EU food legislation. The findings are based on fundamental legal analyses. They are combined with the following three empirical case studies: premarket approval schemes, for novel foods in particular; the application of the EU food hygiene package in the dairy sector in selected regions in Italy and France; and private standards in the Dutch dairy sector. The book shows that compliance by the EU legislator and authorities with EU food law principles and requirements is key to improving the position of food businesses."--Publisher's description